Continuous-time delta-sigma modulator in advanced digital CMOS process - Qiu, Xiaobo (2011)
The rapid development of fast digital signal processors implemented in Complementary metal-oxide-semiconductor (CMOS) very-large-scale integration (VLSI) technology has dramatically increased the demand for high speed and high resolution analog-to-digital converters (ADCs). These ADCs can be integrated in the fabrication technologies and optimized for digital circuit and systems. As the scaling of the VLSI technology also severely constrains the available dynamic range for the interface of the analog and digital signals, the ADCs are the bottleneck in most of the mixed-signal designs. One of the ADC architectures, delta-sigma oversampling ADCs realize an optimum tradeoff between circuit complexity, cost, and power dissipation. High accuracy is achieved with low precision analog components.